Design and Manufacturing of Bottle Roller Machine for Laboratory Leaching Process by Using Recycled Materials - Tiara Triana; Tubagus Maulana Ichsan; Muhammad Ikramullah; Defita Harun; Muhammad Dzafif Ghifari (Universitas Sultan Ageng Tirtayasa, 2022)
Bottle roll is the equipment used for laboratory metal leaching tests. Leaching is a widely used metal extraction process by dissolving metal from ore using certain chemical reagents. The working principle of the bottle roll is to stir the bottle filled with a suspension sample and place it on rolls that rotate horizontally. In this research, the rotating rolls were driven by a recycled water pump electric motor which is transmitted using a pulley and belt. The research objective is to create a bottle roll machine that is practically easy and safe to carry out the leaching test or any other tests that involve agitation, especially for process engineering students. The performance validation of the equipment was done by conducting some leaching tests using the manufactured bottle roll to determine the consistency of the roll rotation, as leaching tests are generally done for a quite long period, usually 24 hours continuously. The sand sample was sieved into 100 mesh of particle size and then mixed with water to make a suspension. The suspensions were put into 2.5 liters of used glass chemical bottles and 1 liter HDPE plastic bottles with various diameters of 14 Cm, 12 Cm, and 8 Cm. The results showed that the machine could perform the leaching test at best in HDPE bottles with an average of 31 RPM of rotation speed tested for 24 hours.